Effectiveness of the E-Peken Platform as a Means of Online Marketing Success for Grocery Stores UMKM in Wiyung District, Surabaya - Kinanti, Anggreini Ratna; Kusumasari, Indah Respati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effectiveness of the e-Peken platform as an online marketing tool for MSME grocery stores in Wiyung District, Surabaya City. A descriptive qualitative approach was used, with data collection techniques through in-depth interviews with grocery store owners who use e-Peken and officials/employees of the Surabaya Department of Cooperatives, Small and Medium Enterprises, and Trade (Dinkopdag), accompanied by observation and documentation. The results show that e-Peken contributes to increasing business visibility and expanding consumer reach, although sales growth is not evenly distributed. The level of ease of use is relatively good for entrepreneurs who are familiar with technology, but limited digital literacy and devices remain obstacles. The socialization and mentoring program from Dinkopdag has been running, but its sustainability needs to be strengthened to optimize platform utilization. The findings also indicate the need for feature development, integrated promotional strategies, and technical support that adapt to MSME capacity. This study emphasizes the importance of synergizing local government digital policies to accelerate the marketing transformation of locally-based MSMEs.